The Impacts of Emotional Labor, Social Relationships, and Working Conditions on Psychological Burnout in Korean Childcare Teachers - Jinwook Kim; Mihwa Lee; Youjeong Park (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aimed to investigate the relative impacts of personal factors (marital status, age of children taught, type of childcare center, and emotional labor), work-related social relationships, and working conditions on psychological burnout in Korean childcare teachers. A total of 496 teachers working in various types of childcare centers were surveyed in South Korea. The following results were obtained: First, teachers’ psychological burnout differed with their marital status, the age of the children taught, and the type of childcare center. Second, teachers’ psychological burnout was positively associated with their emotional labor, but negatively associated with workrelated social relationships and working conditions. Third, teachers’ marital status, emotional labor, social relationships (with co-workers and parents), and working conditions affected their psychological burnout. Working conditions had the largest explanatory power on the variance of teacher burnout, followed by social relationships. The results suggest that efforts to improve working conditions along with social relationships among childcare teachers are most important to lessen the level of burnout in childcare teachers.